Regulation of SIV Antigen-Specific CD4+ T Cellular Immunity via Autophagosome-Mediated MHC II Molecule-Targeting Antigen Presentation in Mice - Jin, Yi (Public Library of Science, 2014)
CD4+ T cell-mediated immunity has increasingly received attention due to its contribution in the control of HIV viral replication; therefore, it is of great significance to improve CD4+ T cell responses to enhance the efficacy of HIV vaccines. Recent studies have suggested that macroautophagy plays a crucial role in modulating adaptive immune responses toward CD4+ T cells or CD8+ T cells. In the present study, a new strategy based on a macroautophagy degradation mechanism is investigated to enhance CD4+ T cell responses against the HIV/SIV gag antigen. Our results showed that when fused to the autophagosome-associated LC3b protein, SIVgag protein can be functionally targeted to autophagosomes, processed by autophagy-mediated degradation in autolysosomes/lysosomes, presented to MHC II compartments and elicit effective potential CD4 T cell responses in vitro. Importantly, compared with the SIVgag protein alone, SIVgag-LC3b fusion antigen can induce a stronger antigen-specific CD4+ T cell response in mice, which is characterized by an enhanced magnitude and polyfunctionality. This study provides insight for the immunological modulation between viral and mammalian cells via autophagy, and it also presents an alternative strategy for the design of new antigens in the development of effective HIV vaccines.